Development of oxidative stress in rats of different sexes subjected to immobilization stress of different durations - Denefil, O.; Pokryshko, A. (Journal of Education, Health and Sport, 2023)
Introduction. The problem of stress is currently one of the main problems not only in Ukraine, but also in the whole world. True, stress does not lead to damage in everyone, some adapt to stress. Studying the impact of different durations of stress, in particular, clarifying the mechanisms of their impact on the body, is relevant. The purpose of the study is to evaluate the processes of lipid peroxidation in the blood of rats of different sexes that have experienced stress of different durations. Materials and methods. Experiments were performed on 56 white male Wistar rats aged 3.5-4 months. The animals were divided into 4 groups: 1 – control, 2 – stress during 1 hour (Stress 1), 3 – stress during 2 hours (Stress 2), 4 – stress during 3 hours (Stress 3). Stress was induced by gently fixing the animal's on a plate with its back down. Superoxide dismutase and catalase activity (SOD, CAT), the concentration of diene and triene conjugates (DC, TC), Schiff's bases (SB), TBA-active products (TBA-ap) were determined in blood serum. Research results and their discussion. In male rats with Stress 1, compared to the control, there was an increase of DC by 11.1%, TC – by 14.9%, SB – by 26.3%, TBA-ap – by 27.5%, SOD – by 12.5%, CAT – by 31.3%. In female rats with Stress 1, compared to the control, there was an increase in DC by 4.2%, TC – by 8.9%, SB – by 45.2%, TBA-ap – by 14.1%, SOD – by 15.5%, and CAT – by 7.3%. Such results indicated greater activation of lipid peroxidation processes in males and greater activation of antioxidants in females. In males with Stress 2, compared to the control, the content of DC increased by 83.1%, TC – by 97.4%, SB – by 65.1%, TBA-ap – by 2.6 times, SOD decreased by 9.5%, CAT increased by 44.5%. In females with Stress 2 the content of DC increased by 30.3%, TC – by 28.2%, SB – by 35.5%, TBA-ap – by 85.6%. SOD was at the same level as in the control, CAT increased by 23.1%. Such results indicated a greater activation of lipid peroxidation processes in males and a decrease in their antioxidant activity. In males with Stress 3, compared to the control, the content of DC increased by 2.6 times, TC – by 2.8 times, SB – by 75.8%, TBA-ap – by 3.2 times. SOD decreased sharply by 41.9%, and CAT increased by 66.6%. In females with Stress 3 the content of DC increased by 2.5 times, TC – by 2.5 times, SB – by 45.2%, TBC-ap – by 2.9 times. SOD sharply decreased by 19.6%, and CAT increased by 35.4%. Such results indicated a significant activation of lipid peroxidation processes when antioxidant activity was depleted in males. It was also noted the presence of erosions on the mucous membrane precisely during stress lasting 3 hours, when spot hemorrhages appeared after 2 hours, and hyperemia of the gastric mucosa - after 1 hour. Conclusion. Animals adapt to stress lasting 1 hour. With stress that lasts for 2 hours, disadaptation of animals occurs. With stress that lasts for 3 hours, the animal's body becomes exhausted. In male rats, lipid peroxidation processes occur at a higher level, compared to females.